PENGARUH KEBIJAKAN UPAH KETENAGAKERJAAN TERHADAP KESEJAHTERAAN PEGAWAI PEMERINTAH - Nikmah Dalimunthe; Yasmin Afifah (Politeknik Bisnis Indonesia, 2024)
This study examines the impact of labor wage policy on the welfare of government employees. The study employs a qualitative method, utilizing descriptive data and descriptive methods. The data is sourced from various books, journals, and academic works that can be used as references. The results show a complex relationship between labor wage policy and the welfare of government employees. An increase in the minimum wage, although increasing purchasing power and job satisfaction, raises concerns about inflation and government financial burden. Health and education allowances, on the other hand, significantly improve the quality of life of government employees and their families. Performance incentives, if designed correctly, can boost motivation and work performance.